ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN DAN KOTA DI PROVINSI ACEH TAHUN 2015-2017 - Muarif, Muarif; Indriani, Mirna (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
Local governments in analyzing the financial state is to perform financial ratio analysis. This financial ratio is then used as a benchmark for analyzing the performance of local governments to see how the government manages its regional finances. This study aims to describe the financial performance of municipal and district governments in Aceh Province if measured using independence ratios, effectiveness ratios and growth ratios. 2015-2017 and the relationship between these ratios. The method used is descriptive quantitative to measure financial performance with ratio and financial analysis. The results of the study show that the independence ratio analyzed for District and City Governments in the Province of Aceh in 2015-2017 illustrates very low criteria. Based on the effectiveness ratio in 2015, 15 districts / cities can be classified as very effective and 7 districts and cities which are classified as quite effective. Based on the 2015 PAD growth ratio, the highest was Pidie Jaya Regency with 49%, whereas in 2016 North Aceh Regency became the highest level of PAD growth ratio of 100%, in 2017 East Aceh Regency became the highest at 62%. Then it can be concluded that the more effective the ability of local governments to realize PAD, the higher the growth of PAD will be.